Workplace Justice and Job Satisfaction As Predictors of Satisfaction with Union and Management - Fryxell, Gerald E.; Gordon, Michael E. (Academy of Management Journal, 1989)
This research examined the extent to which workplace justice and job satisfaction predicted satisfaction with union and management. We defined workplace justice in terms of the procedural and distributive justice afforded by an organization's grievance system and, more generally, in terms of beliefs about a moral order in the workplace. Multivariate analyses were used to test a number of hypotheses about the relationships among measures of institutional satisfaction, job satisfaction, and workplace justice. The amounts of procedural and distributive justice afforded by a grievance system were the strongest predictors of satisfaction with a union, whereas belief in a moral order at a workplace was the strongest predictor of satisfaction with management.